Effects of Genotype and Sex on Lipid Oxidation and Fatty Acid Profile of Chicken Breast Meat - Djilali, Benabdelmoumene; Benmehel, Benakriche; Farouk, Beghdadi; Miloud, Halbouche (Pakistan Journal of Nutrition, 2016)
Total lipids, composition of fatty acids and an estimation of degree of oxidation were determined for both sexes in the muscles of Naked Neck (NaNa) local chickens and in another common chicken breed, the Isa Brown (ISA). The lowest content of total lipids and the highest content of unsaturated fatty acids were found in the muscle of the Naked Neck. Twenty-five fatty acids were quantified in the TL from the Naked Neck and higher concentrations of polyunsaturated fatty acids (PUFAs), essential fatty acids (EFAs) and linolenic acids (AA) were found in the total lipids from the Naked Neck than in the muscle from the other chicken breed. Oleic and linoleic acid were found to be the dominant PUFAs in the total lipids from all breeds, with the highest MUFA content in the breast meat from the Naked Neck. The concentration of long chain n-3 fatty acids is considerably higher in Naked Neck meat than in the Isa Brown. The total lipids from the Naked Neck were found to have anti-fatigue and anti-hypoxic activities and to inhibit isoproterenol-induced oxygen consumption. These results indicate that the Naked Neck chicken has superior quality and bioactivity compared to the Isa Brown breed.